ORGAN-PRESERVING MICROSURGERY FOR PLEOMORPHIC ADENOMA OF THE PAROTID SALIVARY GLAND - D.V. Steblovsky (Проблеми екології та медицини)
Of the total number of salivary gland tumors, the parotid gland is affected by the tumoral process in 76.4–90% of cases. Among benign tumors of the parotid gland, the most frequent tumor (61.2–90%) is pleomorphic adenoma. The aim of the research is to develop and apply in clinical conditions microsurgical methods of organ-preserving surgery for pleomorphic adenomas of the parotid gland, to determine the main clinical indications for the use of a specific method of surgical treatment, to reduce the risk of developing postoperative complications. The material of this study is based on the results of the surgical treatment of 90 patients with pleomorphic adenomas of the parotid gland, which was carried out in the clinic of maxillofacial surgery on the basis of the Department of Maxillofacial Surgery of MI “Poltava M.V. Sklifosovskyi Regional Clinical Hospital”. Preoperative diagnosis was made on the basis of clinical examination, results of ultrasound and magnetic resonance computer tomography of the parotid glands, as well as the cytological examination of material obtained during puncture biopsy of the tumor. In 80 patients, the tumor was localized in the superficial part, and in 7 patients – in the deep part of the parotid gland. In 2 patients, there was total tumor damage to almost the entire gland; in 1 patient, the multinodular nature of the tumor process in both the superficial and deep parts of the gland was noted. As a result of the conducted research, we believe that performing a partial resection of the parotid gland using microsurgical principles of the operation allows us to expand the generally accepted indication (tumors up to 2 cm in size) for performing this operation for pleomorphic adenomas of the superficial part of the gland. In our opinion, the main criterion for the use of this operation is the absolute size of the tumor and the relative percentage of tumor involvement in the superficial part of the parotid gland. If the results of the examination show that the tumor does not occupy the entire superficial part of the gland, and it can be removed within the limits of healthy tissues while preserving some part of the gland, preference should be given to this method, rather than subtotal resection of the gland. As a rule, this is possible when such tumors (more than 2 cm) are localized in the region of the poles of the gland.